2022
DOI: 10.3991/ijim.v16i03.28961
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Augmented Reality into MOOC’s in Vocational Education to Support Education 3.0

Abstract: This research discoverable (1) the development of a MOOC (Massive Open Course Online) learning innovation that incorporates Augmented Reality; (2). The use of the concept of AI Injected e-Learning (The Future of Online Education) in Vocational High Schools, which supports the idea of Education 3.0. This study employs a quantitative method to educational research and development, with research sample vocational students. The findings of this research lead to the following conclusions: (1) The efficacy and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…And this study has also found that the AR-CBL application supports an intuitive and interesting learning process for children with special needs by combining the real world and the virtual world. This is in line with the findings of (Nidhom et al, 2022;Widiaty et al, 2021). The implications of this study indicate that the use of the richest reality (augmented reality) in competency-based learning can improve students' skills in understanding and applying computer network concepts in vocational education.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And this study has also found that the AR-CBL application supports an intuitive and interesting learning process for children with special needs by combining the real world and the virtual world. This is in line with the findings of (Nidhom et al, 2022;Widiaty et al, 2021). The implications of this study indicate that the use of the richest reality (augmented reality) in competency-based learning can improve students' skills in understanding and applying computer network concepts in vocational education.…”
Section: Discussionsupporting
confidence: 92%
“…Information and communication technology (ICT) can provide various advantages in supporting the achievement of competencies by learners. Integrating augmented reality (AR) media in competency-based learning models can provide a more in-depth learning experience and enrich student interaction and learning materials (Mubai et al, 2020;Nidhom et al, 2022;Widiaty et al, 2021). Using augmented reality technology, learners can experience interactive simulations that approach real situations related to the competencies being studied.…”
Section: Introductionmentioning
confidence: 99%
“…Students have difficulty understanding TPACK competencies. Several improvements have been made to education in order to align it with the rapid development of technology [56]. Pre-service teachers with a strong understanding of technology will have a deeper understanding of pedagogy and subject [57].…”
Section: Discussionmentioning
confidence: 99%
“…In modern vocational education, it's becoming increasingly difficult for traditional teaching methods to meet the ever-changing educational needs [1] [2], especially in the context of Industry 4.0, it is required that vocational education keep up with the pace of the era and adapt to the needs in the training of new techniques and skills [3][4][5]. However, current teaching systems usually lack the flexibility or adaptability to cope with the personal needs of different students [6][7][8], so it is a beneficial exploration to introduce the hybrid framework of reinforced learning and deep learning into smart teaching systems [9][10][11].…”
Section: Introductionmentioning
confidence: 99%